Concomitant carotid endarterectomy and coronary artery bypass grafting. Own experience - Janczak, Dariusz; Król, Piotr; Skiba, Jacek; Mak, Marek (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2012)
Hemodynamically significant carotid artery stenosis is an important risk factor for neurological complications in the perioperative period in patients undergoing coronary artery bypass grafting (CABG). The authors evaluated the number of neurological complications in a group of 65 patients who had undergone synchronous carotid endarterectomy and coronary revascularization. There were also attempts to answer the question whether internal carotid artery endarterectomy (CEA) performed using so-called drain flow (shunt) increases the risk of neurological complications in the perioperative period.